Perlindungan Konsumen terhadap Produk Makanan Repacking Menurut Hukum Keamanan Pangan dan Obat - Dita Nur Haerunisa; Ruli Purwanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is motivated by the rampant circulation of repackaged products that have not been fully supervised. Therefore, it is necessary to analyze the legal protection provided to consumers and the effectiveness of the role of the Food and Drug Supervisory Agency (BPOM) in conducting supervision. The purpose of this study is to determine the legal protection provided to consumers of packaged food products and to determine the extent to which BPOM carries out its role as a supervisory agency in ensuring the safety of these products. This research uses a normative legal approach with a qualitative approach, through literature study and interviews as a complement. The results show that business actors are required to re-register repackaged products in accordance with food safety regulations. This is a preventive measure to ensure that products in circulation are safe for consumption and provide effective legal protection for consumers. The findings also indicate that BPOM supervision still needs strengthening, both in terms of regulations, resources, and community outreach.